The association between CPR quality of In-hospital resuscitation and sex: A hypothesis generating, prospective observational study - Ziv Dadon; Tal Fridel; Sharon Einav (Resuscitation Plus, 2022)
Introduction: The relationship between sex and cardiopulmonary resuscitation (CPR) outcomes remains unclear. Particularly, questions remain regarding the potential contribution of unmeasured confounders. We aimed to examine the differences in the quality of chest compression delivered to men and women. Methods: Prospective study of observational data recorded during consecutive resuscitations occurring in a single tertiary center (Feb-1-2015 to Dec-31-2018) with real-time follow-up to hospital discharge. The studied variables included time in CPR, no-flow-time and fraction, compression rate and depth and release velocity. The primary study endpoint was the unadjusted association between patient sex and the chest compression quality (depth and rate). The secondary endpoint was the association between the various components of chest compression quality, sex, and survival to hospital discharge/neurologically intact survival. Results: Overall 260 in-hospital resuscitations (57.7% male patients) were included. Among these 100 (38.5%) achieved return of spontaneous circulation (ROSC) and 35 (13.5%) survived to hospital discharge. Female patients were significantly older. Ischemic heart disease and ventricular arrhythmias were more prevalent among males. Compression depth was greater in female vs male patients (54.9 ± 11.3 vs 51.7 ± 10.9 mm; p = 0.024). Other CPR quality-metrics were similar. The rates of ROSC, survival to hospital discharge and neurologically intact survival did not differ between males and females. Univariate analysis revealed no association between sex, quality metrics and outcomes. Discussion: Women received deeper chest compressions during in-hospital CPR. Our findings require corroboration in larger cohorts but nonetheless underscore the need to maintain high-quality CPR in all patients using real-time feedback devices. Future studies should also include data on ventilation rates and volumes which may contribute to survival outcomes.